Bridging evidence-practice gaps: improving use of medicines in elderly Australian veterans - Roughead, Elizabeth E; Kalisch Ellett, Lisa M; Ramsay, Emmae N; Pratt, Nicole L; Barratt, John D; LeBlanc, Vanessa T; Ryan, Philip; Peck, Robert; Killer, Graeme; Gilbert, Andrew L (BMC health services research, 2013)
Background The Australian Government Department of Veterans’ Affairs (DVA) funds an ongoing health promotion based program to improve use of medicines and related health services, which implements interventions that include audit and feedback in the form of patient-specific feedback generated from administrative claims records. We aimed to determine changes in medicine use as a result of the program. Methods The program provides targeted patient-specific feedback to medical practitioners. The feedback is supported with educational material developed by a clinical panel, subject to peer review and overseen by a national editorial committee. Veterans who meet target criteria also receive educational brochures. The program is supported by a national call centre and ongoing national consultation. Segmented regression analyses (interrupted time series) were undertaken to assess changes in medication use in targeted veterans pre and post each intervention. Results 12 interventions were included; three to increase medicine use, seven which aimed to reduce use, and two which had combination of messages to change use. All programs that aimed to increase medicine use were effective, with relative effect sizes at the time of the intervention ranging from 1% to 8%. Mixed results were seen with programs aiming to reduce inappropriate medicine use. Highly specific programs were effective, with relative effect sizes at the time of the intervention of 10% decline in use of NSAIDs in high risk groups and 14% decline in use of antipsychotics in dementia. Interventions targeting combinations of medicines, including medicine interactions and potentially inappropriate medicines in the elderly did not change practice significantly. Interventions with combinations of messages targeting multiple components of practice had an impact on one component, but not all components targeted. Conclusions The Veterans’ MATES program showed positive practice change over time, with interventions increasing use of appropriate medicines where under-use was evident and reduced use of inappropriate medicines when single medicines were targeted. Combinations of messages were less effective, suggesting specific messages focusing on single medicines are required to maximise effect. The program provides a model that could be replicated in other settings.